2003
DOI: 10.1002/mrc.1318
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for spin diffusion in a H,H‐NOESY study of imidazolium tetrafluoroborate ionic liquids

Abstract: The ionic liquids 1-ethyl-3-methylimidazolium tetrafluoroborate ([EMIM][BF4]) and 1-methyl-3-propylimidazolium tetrafluoroborate ([PMIM][BF4]) were studied by H,H-NOESY NMR using a cross-relaxation matrix analysis. Cross-peak intensities are seen to increase with increasing mixing time. Experimental and theoretical hydrogen-hydrogen distances are in agreement at short mixing times (50 ms). Mixing times longer than 50 ms result in an increasing contribution of spin diffusion that produces unrealistically short … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
50
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(60 citation statements)
references
References 38 publications
8
50
0
2
Order By: Relevance
“…These results are consistent with the observation of both conformers being simultaneously present in the spectra of the [C 4 mim] þ cation liquids are given in Fig. 13 and the assignments are specified in Table 2, based on the calculations, some of which are summarized in [132][133][134][135][136].…”
Section: Brief Introduction To Ab-initio Model Calculationssupporting
confidence: 88%
“…These results are consistent with the observation of both conformers being simultaneously present in the spectra of the [C 4 mim] þ cation liquids are given in Fig. 13 and the assignments are specified in Table 2, based on the calculations, some of which are summarized in [132][133][134][135][136].…”
Section: Brief Introduction To Ab-initio Model Calculationssupporting
confidence: 88%
“…Other NMR studies of this family of ionic liquids and their mixture with molecular solvents support the occurrence of hydrogen bonding between the imidazolium alkyl groups and the anions [10][11][12][13][14][15]. Among mixtures of ionic liquids with molecular solvents, those with water are especially important as the presence of water in ionic liquids may affect their solvent properties [16][17].…”
Section: Introductionmentioning
confidence: 96%
“…Among mixtures of ionic liquids with molecular solvents, those with water are especially important as the presence of water in ionic liquids may affect their solvent properties [16][17]. To our knowledge, there is no NMR data on mixtures of water and phosphonium ionic liquids, despite extensive NMR studies of imidazoliumbased ionic liquids and their solutions [8][9][10][11][12][13][14][15]. Here, we report the first studies of 1 H NMR chemical shifts of trihexyl (tetradecyl) phosphonium chloride ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…41 Moreover, H,H-NOESY experiments indicate the existence of spin diffusion in 1,3-dialkyimidazolium ionic liquids. 42 Recoil Spectrometry experiments with liquid BMI.PF 6 indicated that bulk stoichiometry is conserved at the surfaces (the surface is neither enriched with the cation nor with the anion). The N-imidazolium atoms and alkyl side chains are deeper in the surface and the average orientation of the cation is with the plane of the ring in the vertical position.…”
Section: Structural Organization In Liquid and Gas Phasementioning
confidence: 99%